Pengaruh Citra Merek Kualitas Pelayanan Dan Kepercayaan Terhadap Loyalitas Pelanggan Pada Konveksi Nuri Collection Di Kabupaten Bangli - I Nyoman Widnyana; Nyoman Dwika Ayu Amrita; I Wayan Meryawan (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Companies are compelled to innovate in order to sustain consumer loyalty in the face of fiercely competitive market conditions brought about by the ever-increasing speed of corporate development. Several aspects, including trust, service quality, and company image, impact the ability to build good client loyalty. The degree to which trust, service quality, and brand image all have partial and simultaneous effects on consumer loyalty is investigated in this study. Using a purposive sampling technique and a total of ninety consumers, this study compiles quantitative data. This research makes use of SPSS 25.00 for Windows to process the data. Various statistical tests, including t-tests, F-tests, multiple linear regression analysis, tests for coefficient of determination, reliability and validity of research equipment, and testing for classical assumptions are used to process the data. The study's findings show that trust, service quality, and brand image all contribute to consumer loyalty in their own unique ways. Building a positive reputation for the business, providing excellent customer service, and earning the confidence of consumers are all direct ways to increase customer loyalty, which is very important in the convection industry.